Health-related physical fitness and weight status in 13- to 15-year-old Latino adolescents. A pooled analysis (2019)
Objective: The aim of this study was to investigate the relation between health-related physical fitness and weight status in 13- to 15-year-old Latino adolescents. Method: The final sample consisted of 73,561 adolescents aged 13–15 years (35,175 girls) from Chile (n = 48,771) and Colombia (n = 24,790). Cardiorespiratory and musculoskeletal fitness were measured using 20-m shuttle run (relative peak oxygen uptake – VO2peak) and standing broad jump test (lower body explosive strength), respectively. The International Obesity Task Force definition was used to define weight status (i.e., underweight, normal weight, overweight, and obese). Results: The present study found an inverted J-shape relationship between body mass index, cardiorespiratory fitness, and musculoskeletal fitness in both genders and all age groups (p and lt; 0.01). Results also suggest that underweight adolescents, and not just overweight and obese adolescents, have lower odds of having a healthy cardiorespiratory fitness (based on new international criterion-referenced standards) profile when compared with their normal weight peers, except in girls aged 14 (p = 0.268) and 15 years (p = 0.280). Conclusions: The present results indicate low cardiorespiratory fitness and musculoskeletal fitness levels in underweight, overweight, and obese adolescents when compared with their normal weight peers. The findings appear to suggest that exercise programs should to decrease fat mass in overweight/obese adolescents and increase muscle mass in underweight adolescents. © 2018 Sociedade Brasileira de Pediatria